Surveillance of non-communicable diseases: What matters to users? A qualitative interview study - Robyn Kettlitz; Maike Buchmann; Oktay Tuncer; Laura Krause; Thomas Ziese; Lukas Reitzle (Journal of Health Monitoring)
Background: Surveillance systems for diseases serve as an early warning system and orientation for decision-makers. As part of the National Diabetes Surveillance at the Robert Koch Institute (RKI), existing formats of information transfer were evaluated and an analysis of users’ requirements regarding the dissemination of results of surveillance for non-communicable diseases (NCD) was carried out. Methods: 13 semi-structured guided interviews were conducted with persons from health politics, healthcare, media and science and analysed in a qualitative content analysis (interview survey period: 10/2022 – 01/2023). Results: For all respondents, the frequency of diseases and their determinants, care and consequences were the focus of NCD surveillance. Wider determinants of health and illness situation were also considered relevant. Requirements regarding the presentation of these contents differed between the user groups. Factors that facilitate and inhibit the use of NCD surveillance information were consistent across the user groups. Conclusions: There is a need for the presentation of options for action, especially for users involved in health politics and healthcare. Diabetes surveillance showed that many requirements are already met by the existing formats. Many of the users also wanted the content to be expanded to include other NCD.